2020
DOI: 10.1093/mnras/staa1244
|View full text |Cite
|
Sign up to set email alerts
|

Two Wolf–Rayet stars at the heart of colliding-wind binary Apep

Abstract: Infrared imaging of the colliding-wind binary Apep has revealed a spectacular dust plume with complicated internal dynamics that challenges standard colliding-wind binary physics. Such challenges can be potentially resolved if a rapidly-rotating Wolf-Rayet star is located at the heart of the system, implicating Apep as a Galactic progenitor system to long-duration gamma-ray bursts. One of the difficulties in interpreting the dynamics of Apep is that the spectral composition of the stars in the system was uncle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 57 publications
10
42
1
Order By: Relevance
“…This result rules out the possibility of the secondary component being a neutron star or a black holewhich could conceivably drive a spiral plume by gravitational reflex motion, analogous to that witnessed in some mass-losing red giant systems such as AFGL 3068 (Mauron & Huggins 2006) -or that of a single-star dust production mechanism driving the prominent spiral nebula. This conclusion is supported by the findings of Callingham et al (2020), in which an analysis of the visible-infrared spectrum taken with XSHOOTER on the VLT found that the central engine consists of two WR stars of subtypes WC8 and WN4-6b, respectively, identifying Apep as the first double classical WR binary to be observationally confirmed.…”
Section: Detection Of Apep's Central Binarysupporting
confidence: 64%
See 4 more Smart Citations
“…This result rules out the possibility of the secondary component being a neutron star or a black holewhich could conceivably drive a spiral plume by gravitational reflex motion, analogous to that witnessed in some mass-losing red giant systems such as AFGL 3068 (Mauron & Huggins 2006) -or that of a single-star dust production mechanism driving the prominent spiral nebula. This conclusion is supported by the findings of Callingham et al (2020), in which an analysis of the visible-infrared spectrum taken with XSHOOTER on the VLT found that the central engine consists of two WR stars of subtypes WC8 and WN4-6b, respectively, identifying Apep as the first double classical WR binary to be observationally confirmed.…”
Section: Detection Of Apep's Central Binarysupporting
confidence: 64%
“…To indicate the impact of this on the interpretation, we adjust our earlier ∼6:1 K-band binary flux ratio now recognizing the brighter component flux should be split two ways: a stellar photosphere and resolved dust shell. Performing this decomposition, we find that the embedded point sources are left with an approximately equal flux ratio (∼14 per cent of the total flux in each): a result that can be more neatly brought into accord with expectations from spectroscopic evidence (Callingham et al 2019(Callingham et al , 2020.…”
Section: Filter Namementioning
confidence: 51%
See 3 more Smart Citations